2012
DOI: 10.1088/0004-637x/761/2/104
|View full text |Cite
|
Sign up to set email alerts
|

Interplanetary Propagation of Solar Energetic Particle Heavy Ions Observed at 1 Au and the Role of Energy Scaling

Abstract: We have studied ∼0.3 to >100 MeV nucleon −1 H, He, O, and Fe in 17 large western hemisphere solar energetic particle events (SEP) to examine whether the often observed decrease of Fe/O during the rise phase is due to mixing of separate SEP particle populations, or is an interplanetary transport effect. Our earlier study showed that the decrease in Fe/O nearly disappeared if Fe and O were compared at energies where the two species interplanetary diffusion coefficient were equal, and therefore their kinetic ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 104 publications
(157 reference statements)
3
27
0
1
Order By: Relevance
“…The more gradual increase observed at L1 for low-energy protons (bottom panel of Figure 1(c)) and low-energy ions (Figure 8(c)) with respect to the faster increase observed for electrons (Figure 8(a)) and high-energy ions and protons (Figures 8(a) and (c)) may be due to a rigidity-dependent transport for the particles to escape from the shock front. Similar differences in low and high energy ion intensities were observed for the event on 2005 January 20 (e.g., Figure 2 in Mason et al 2012). …”
Section: Discussionsupporting
confidence: 75%
“…The more gradual increase observed at L1 for low-energy protons (bottom panel of Figure 1(c)) and low-energy ions (Figure 8(c)) with respect to the faster increase observed for electrons (Figure 8(a)) and high-energy ions and protons (Figures 8(a) and (c)) may be due to a rigidity-dependent transport for the particles to escape from the shock front. Similar differences in low and high energy ion intensities were observed for the event on 2005 January 20 (e.g., Figure 2 in Mason et al 2012). …”
Section: Discussionsupporting
confidence: 75%
“…On the other hand, these injection times are inferred by fitting to the observations from the event onset through the peak (that are likely dominated by particles with little/weak scattering), not to the observations in the decay tail (that are probably dominated by scattered/reflected particles). Future investigations of detailed particle propagation will require a focused transport modeling (including the effects of adiabatic cooling, magnetic focusing, and pitch angle scattering) (e.g., Zhang 1999; Qin et al 2006;Li 2008;Mason et al 2012), which exceeds the scope of this paper.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Next, we point out that the increases in the Fe/O ratio observed during the early phases of large SEP events has been successfully and quantitatively modeled in many studies as a transport effect (e.g., Tylka et al 1999Tylka et al , 2005Tylka et al , 2012Mason et al 2012Mason et al , 2014Reames et al 2013), and that in particular, the following three observational results in conjunction with the new results presented in this paper provide strong support for the counterargument that ∼0.1-500 MeV nucleon −1 H-Fe nuclei observed during large gradual SEPs are indeed accelerated by near-Sun CME-driven shocks. Thus, the bulk of the observations show that the suggestion that hypothesized "flare" contributions dominate the early phases of SEP event composition or the event-integrated SEP Fe/O abundances is not supported.…”
Section: ∼25-80 Mev Nucleonmentioning
confidence: 95%
“…2. Second, many studies (e.g., Tylka et al 1999;Mason et al 2006Mason et al , 2012Reames 2015) have shown that temporal variations in the <100 MeV nucleon −1 Fe/O abundances in large SEP events are diminished or even eliminated if the Fe and O time-intensity profiles are compared at a scaled energy for the different species, indicating that these variations are due to differences in the Q/M ratios of the different species, and therefore better explained by interplanetary transport models that include the effects of focusing, diffusion, convection, adiabatic deceleration, and pitch-angle scattering. 3.…”
Section: ∼25-80 Mev Nucleonmentioning
confidence: 99%
See 1 more Smart Citation